2011
DOI: 10.4103/0019-509x.84932
|View full text |Cite
|
Sign up to set email alerts
|

Time trend in frequency of occurrence of major immunophenotypes in paediatric acute lymphoblastic leukemia cases as experienced by Cancer Institute, Chennai, south India during the period 1989-2009

Abstract: We find that this change of pattern is synchronizing with the socioeconomic and industrial development prevailing in our geographic setting and suggest a possible link between the predominant immunophenotype of pediatric ALL cases and the environmental and socioeconomic factors prevailing in that locality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Western data clearly shows a higher incidence of B-ALL over T-ALL. However many older studies done among Asian, African and middle eastern populations have shown a higher incidence of T-ALL [5][6][7]. Our data also show a higher incidence in the B-ALL category with frequencies similar to that reported in the Americas and Europe.…”
Section: Immunophenotypesupporting
confidence: 87%
See 2 more Smart Citations
“…Western data clearly shows a higher incidence of B-ALL over T-ALL. However many older studies done among Asian, African and middle eastern populations have shown a higher incidence of T-ALL [5][6][7]. Our data also show a higher incidence in the B-ALL category with frequencies similar to that reported in the Americas and Europe.…”
Section: Immunophenotypesupporting
confidence: 87%
“…However there is evidence to state that the geographic difference in incidence is more likely due to the socioeconomic status of the population than ethnicity. This was highlighted by two independent studies carried out in south and north India, that showed the change in trends from T-All to B-ALL with the changing socioeconomic status of a single concerned population [5,6]. Similar changes have been observed in other developing nations [4].…”
Section: Immunophenotypementioning
confidence: 74%
See 1 more Smart Citation
“…[6] In India also, studies reported from Tata Memorial Hospital, Mumbai, All India Institute of Medical Sciences, New Delhi and Cancer Institute, Chennai revealed a declining trend of T-ALL accompanied by an increasing trend in B-ALL among children. [789] Thus most of these studies have focused predominantly on B-ALL. Moreover, in the existing scenario, specific outcome data for adolescents was relatively sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Although this provides an excellent opportunity for evaluating unique contributions of prognostic factors within each immunophenotype group, direct comparison of outcome between T and B lineage becomes difficult because of the different treatment regimen used. Furthermore, there is paucity of data addressing clinical features, prognostic parameters and outcome of T ALL in developing countries like India, where this ALL subtype is more frequently observed than in the developed nations (16,17) . Disease free survival and event free survival were higher in B ALL in adolescent patients as compared to T ALL who had significantly low survival rates (18) .…”
Section: Discussionmentioning
confidence: 99%